The Role of Adverbs and Adjectives in English Negation - Mahfood Khalaf Aljuburi (PROSPECTIVE RESEARCHES, 2023)
The present paper tries to deal with English negation as an area of linguistic analysis that still needs to be investigated. A phrase that is negative in meaning which is not accounted for in books of grammar is analyzed as a negator according to the criteria set by grammarians and we might possibly find other parts of speech which carry negation. Another aspect of local negation is introduced to prove that this is another example in favour of the hypothesis that negation is yet to be studied. By studying such phenomena the paper also suggests that grammar cannot be separated from semantics in the study of language. The findings of the study show that the analysis of the phrase far from and the effect of only after a clause negator resulted in uncovered case of local negation all of which suggest that negation is understudied and under researched.